1982
DOI: 10.1128/jcm.16.5.959-961.1982
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two methods for enumeration of mycoplasmas

Abstract: Two methods of viable cell counts were evaluated for Mycoplasma hominis and Ureaplasma urealyticum: color change unit50 and colony-forming unit. The color change unit5O method gave higher estimates of cell numbers; furthermore, the color change unit5O values correlated better with the DNA content of the cell pellet and the published genome sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 14 publications
0
36
0
Order By: Relevance
“…-10 6 M. pneumoniae CCU(Stemke & Robertson, 1982) was added apically to initiate infections (eight wells per strain, dilution, and time point). For some experiments, we included infections initiated with 10 3 or 10 9 CCU, as indicated.…”
mentioning
confidence: 99%
“…-10 6 M. pneumoniae CCU(Stemke & Robertson, 1982) was added apically to initiate infections (eight wells per strain, dilution, and time point). For some experiments, we included infections initiated with 10 3 or 10 9 CCU, as indicated.…”
mentioning
confidence: 99%
“…The GC ⁄ CFU ratios observed in this study for several mycoplasmas are in good concordance with the GC ⁄ CFU and GC ⁄ colour changing units (CCU) previously determined for Ureaplasma urealyticum and Myc. hominis (Stemke and Robertson 1982). The results of that study showed the ratios between genome equivalents (calculated on basis of the amount of isolated genomic DNA) and CFU determined for U. urealyticum and Myc.…”
Section: Culture With Mammalian Cells (Suspension Of Cho Cells)mentioning
confidence: 87%
“…Mycoplasmas are the smallest and simplest free-living parasitic organisms implicated in a variety of plant and animal diseases . Although several techniques have been proposed to assess the number of cultured Mollicutes cells (Snell 1981;Albers and Fletcher 1982;Stemke and Robertson 1982;Meur et al 1989;Robertson and Stemke 1995;Lin et al 2001) accurate determination of Mycoplasma growth still remains a difficult task (Robertson and Stemke 1995). For example, light microscopy determination is hampered by the small size of these organisms (0AE2-0AE7 lm) and viable cell estimation is additionally complicated by the complex nutritional requirements of Mollicutes cells (Stemke and Robertson 1982;Robertson and Stemke 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Although several techniques have been proposed to assess the number of cultured Mollicutes cells (Snell 1981;Albers and Fletcher 1982;Stemke and Robertson 1982;Meur et al 1989;Robertson and Stemke 1995;Lin et al 2001) accurate determination of Mycoplasma growth still remains a difficult task (Robertson and Stemke 1995). For example, light microscopy determination is hampered by the small size of these organisms (0AE2-0AE7 lm) and viable cell estimation is additionally complicated by the complex nutritional requirements of Mollicutes cells (Stemke and Robertson 1982;Robertson and Stemke 1995). In this context, while protein quantification is a simple and a widely used method to determine cell number, cellular proteins constitute only a small fraction of the total protein concentration of the highly supplemented media required for Mollicutes growth, thus supporting the notion that this approach is unreliable to estimate the growth of these organisms (Robertson and Stemke 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation